Ba2[MoO3(OH)(IO3)2]IO3: A Promising SHG Material Featuring a Λ‑Shaped Functional Motif Achieved by Universal Mono-Site Substitution - Huang, Qian-Ming; Hu, Chun-Li; Yang, Bing-Ping; Tang, Ru-Ling; Chen, Jin; Fang, Zhi; Li, Bingxuan; Mao, Jiang-Gao (Chemistry of materials, 2020)
The first polar alkaline-earth metal molybdenum iodate, Ba2[MoO3(OH)(IO3)2]IO3, with a Λ-shaped [MoO3(OH)(IO3)2]3– functional motif, was rationally designed. A zero-dimensional (0D) [MoO3(OH)(IO3)2]3– unit is derived from 0D [MoO2(OH)(IO3)3]2– polyanion through anionic mono-site substitution. Ba2[MoO3(OH)(IO3)2]IO3 possesses a strong phase-matchable second-harmonic-generation (SHG) response of approximately 8 times that of benchmark KH2PO4 (KDP), a broad transparent spectral region from near-ultraviolet to mid-infrared (0.29–10.6 μm), a large band gap of 3.78 eV, and a high laser-induced damage threshold (LDT) of 92.3 MW cm–2. The results suggest that Ba2[MoO3(OH)(IO3)2]IO3 can be potentially applied in the mid-infrared nonlinear optical field. Theoretical calculations demonstrate that the large SHG response of the title compound originates mainly from the Λ-shaped [MoO3(OH)(IO3)2]3– functional unit. From multisite substitution to mono-site substitution, this work provides a more generic route to synthesize SHG materials.